Containment control of multiple unmanned surface vessels with NN control via reconfigurable hierarchical topology - Liu, Wei; Teng, Fei; Xiao, Huiyu; Wang, Chen (Frontiers in Computational Neuroscience, 2023)
This paper investigates the containment control of multiple unmanned surface vessels with nonlinear dynamics. To solve the leader-follower synchronization problem in containment control system, a hierarchical control framework with topology reconfiguration mechanism is proposed, and the process of containment control is converted into the tracking of reference signal for each vessel on its respective target heading by means of the light-of-sight (LOS) guidance. In control system, the neural networks (NNs) are adopted to consider the uncertainty. In follower layer, a connectivity controller with topology reconfiguration mechanism is embedded, to change the converging positions of followers so as to avoid collision within system, and to maintain the system connectivity when the communication equality is poor. The effectiveness of the hierarchical control framework proposed in this paper is valid by simulation.